Data Compression with High Peak Signal to Noise Ratio Using Bisectional Cylindrical Wavelet Transform For a Satellite Image - Pranitha, K.; Kavya, G. (International Journal of Engineering and Technology, 2018)
Satellite imaging is an energetic way for the analyst to review about the space information, geoscience and space report analysis. Image compression is an essential specification which provides the actual information in transmitted data on earth observation satellites. It takes advantage to reduce the capacity of space info with a unique term intention to lower the memory capacity for intelligence accumulation, moderating, data deportation content modification considering performance transition. Image compression, it helps to obtain the original image file with deficient recognition capacity. Degradation in the content of an image file confesses enhanced images which are directed towards particular storage recognition. Image compression downgrades the content of an image file without depressing the original quality. In this paper, for satellite image compression, existing wavelet transforms like continuous wavelet transform (CWT), stationary wavelet transform (SWT), data compression using 2D wavelet analysis and the proposed method Bisectional cylindrical wavelet transform (BCWT) are performed and compared with the appropriate results. Performance parameters like Peak Signal to Noise Ratio, Signal to Noise Ratio, Maximum Absolute Error, Mean Square Error, Compression Ratio, Bits per Pixel and threshold value are evaluated and tabulated.Â